2016
DOI: 10.1515/shll-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Final devoicing and deletion of /-d/ in Castilian Spanish

Abstract: In the Spanish of north-western Spain, word-final /-d/ shows a remarkable variety of phonetic outcomes. Its possible realizations include voiced approximants, voiceless fricatives and voiced and voiceless plosives, in addition to the deletion of the segment. Here we examine this complex pattern of allophony in a corpus of conversational speech, focusing on the effect of the following phonological context. The results show that most commonly /-d/ is either deleted or realized as a voiceless fricative. Voiceless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Brown (2015), studying spirantization in word-initial /d/, found no significant frequency effect, but rather found that the frequency a word had /d/ occurring in contexts favorable to spirantization influenced whether spirantization occurred when /d/ appeared in unfavorable contexts. Looking at Peninsular Spanish processes affecting word-final /d/, Hualde and Eager (2016) found no significant effect for lexical frequency in their sample.…”
Section: A Usage-based Account Of Spanish /D/ In Contact With Portuguesementioning
confidence: 84%
“…Brown (2015), studying spirantization in word-initial /d/, found no significant frequency effect, but rather found that the frequency a word had /d/ occurring in contexts favorable to spirantization influenced whether spirantization occurred when /d/ appeared in unfavorable contexts. Looking at Peninsular Spanish processes affecting word-final /d/, Hualde and Eager (2016) found no significant effect for lexical frequency in their sample.…”
Section: A Usage-based Account Of Spanish /D/ In Contact With Portuguesementioning
confidence: 84%
“…Although devoicing and fricativization have been attested since the Middle Ages, deletion is a relatively more recent phenomenon, dating to the second half of the 15 th century, and exhibiting lexical effects (Ariza, 2012, p. 154). Of these three processes, fricativization is only observed in Peninsular Spanish (Antón, 1998;García Mouton & Molina Martos, 2015;González, 2002;Hualde & Eager, 2016;Molina Martos, 2016;Navarro Tomás, 1977;Pérez Castillejos, 2012). Devoicing and deletion appear to be more geographically widespread and have been reported to be conditioned by speech style; in particular, deletion is present in informal speech (Hualde & Eager, 2016;Navarro Tomás, 1977, §102;see Molina Martos, 2016, for a distribution of variants in the province of Madrid) and seemingly absent from read speech (González, 2002;Pérez Castillejos, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of these three processes, fricativization is only observed in Peninsular Spanish (Antón, 1998;García Mouton & Molina Martos, 2015;González, 2002;Hualde & Eager, 2016;Molina Martos, 2016;Navarro Tomás, 1977;Pérez Castillejos, 2012). Devoicing and deletion appear to be more geographically widespread and have been reported to be conditioned by speech style; in particular, deletion is present in informal speech (Hualde & Eager, 2016;Navarro Tomás, 1977, §102;see Molina Martos, 2016, for a distribution of variants in the province of Madrid) and seemingly absent from read speech (González, 2002;Pérez Castillejos, 2012). More importantly for the present study, two additional factors condition this process: deletion is more frequent in absolute word-final position than within a phrase (Navarro Tomás, 1977, §102; see Hualde & Eager, 2016, for experimental data), and conditioned by the specific lexical item.…”
Section: Introductionmentioning
confidence: 99%
“…This phonological devoicing is generally thought not to have a phonetic motivation word-finally. Instead, it is hypothesized that there is a phonetic motivation only utterancefinally, due to the approach to the following pause (Hock 1991(Hock , 1999Hualde and Eager 2016). There is thus utterance-final breathy voice or partial, phonetically variable amounts of devoicing, which arise in what can be described as as near to assimilation to silence as possible (Hock 1991, 1999, Hualde and Eager 2016, Keating 1988, Lieberman 1967, Myers and Padgett 2014.…”
mentioning
confidence: 99%
“…In the analogy theory, after this initial inherent phonetic push toward devoicing utterancefinally then the phenomenon can be phonologized utterance-finally, and analogized down to lower domain levels (Hock 1991, 1999, Hualde and Eager 2016. The analogy hypothesis provides a motivation and explanation for how phonological final devoicing is found at the right edges of words, when this would seemingly interfere with an inherent pressure to maintain voicing between voiced sounds, which phonological final devoicing interferes with in some cases.…”
mentioning
confidence: 99%